Is high accuracy of Vesical Imaging-Reporting and Data System (VI-RADS) sufficient for its implementation in the urological practice? - Katerina Rysankova; Pavla Hanzlikova; Vladimir Zidlik; Adela Vrtkova; Maryna Slisarenko; Jozef Skarda; Michal Grepl; Jan Krhut (Biomedical Papers, 2023)
Aims. Currently, the only method used to differentiate between MIBC and NMIBC is transurethral resection of the bladder tumour (TURBT). Magnetic resonance and Vesical Imaging-Reporting and Data System (VI-RADS) would allow for discrimination between NMIBC and MIBC. We evaluate the sensitivity and specificity of VI-RADS in the diagnosis of muscle-invasive bladder cancer and discuss its value in everyday urological practice. Methods. 64 patients with bladder cancer (BC) were enrolled into this prospective study. Multiparametric magnetic resonance imaging (mpMRI) was performed before transurethral resection of the bladder tumour (TURBT) and evaluated using the VI-RADS score. Score were compared to histopathology results. We evaluated the sensitivity, specificity, positive and negative predictive value of this system using both cut-off VI-RADS ≥ 3 and ≥ 4. Results. Sensitivity of 92.3% (95%CI: 64.0; 99.8), specificity of 81.4% (95%CI: 69.1; 90.3), positive predictive value of 52.2% (95%CI: 30.6; 73.2) and negative predictive value of 98.0% (95%CI: 89.1; 99.9) was determined using cut off VI-RADS ≥ 3, while sensitivity of 76.9% (95%CI: 46.2; 95.0), specificity of 91.5% (95%CI: 81.3; 97.2), positive predictive value of 66.7% (95%CI: 38.4; 88.2), and negative predictive value of 94.7% (95%CI: 85.4; 98.9) was determined using cut-off VI-RADS ≥ 4. Based on our results, we consider the optimal cut-off point to be VI-RADS ≥ 3 with the overall prediction accuracy of 83.3% (95%CI: 72.7; 91.1). Conclusions. We acknowledge that mpMRI provides valuable information with regard to BC staging, however, despite its high overall accuracy, we do not consider the VI-RADS could replace TURBT in discrimination between non-muscle invasive and MIBC.